A case of Hyper-IgE syndrome with a mutation of the STAT3 gene - Ji-man Kang; Jungmun Suh; Jihyun Kim; Hee-Jin Kim; Yae-jean Kim; Hun Seok Lee; Young Kee Shin; Kangmo Ahn; Sang-Il Lee (Korean Journal of Pediatrics, 2010)
Hyperimmunoglobulin E syndrome (HIES) is a rare immunodeficiency disease which is characterized by high serum IgE levels, eczema, and recurrent infections. Herein we present the case of a patient with HIES associated with STAT3 gene (stat3) mutation. A 16 year-old girl was admitted to our hospital due to hemoptysis caused by pneumonia with bronchiectasis. She had a history of recurrent skin and respiratory tract infections, such as pneumonia caused by MRSA (methicillin-resistant Staphylococcus aureus) and Pseudomonas aeruginosa. On physical examination, a broad round shaped nose, oral thrush, and chronic eczematous skin rash over her whole body were found. Laboratory data showed an elevated eosinophil count (750/µL) and total IgE level (5,001 U/mL). The patient’s National Institutes of Health (NIH) score for HIES was 44. Direct sequencing of the STAT3 gene revealed that the patient was heterozygous for a missense mutation in the DNA binding domain of the STAT3 protein (c.1144C>T, p. Arg382Trp). HIES should be suspected in patients with recurrent infections and can be confirmed by clinical scoring and genetic analysis.